The U.S. Secondary Sanctions Related to Russia: Empirical Analysis - I. N. Timofeev (Сравнительная политика, 2024)
The U.S. Administration has been increasingly using secondary sanctions to make legal persons in foreign jurisdictions comply with the U.S. regimes of economic restrictive measures. The practice of secondary sanctions has been towering since the outbreak of Russia’s special military operation in Ukraine. Hundreds of companies in third jurisdictions found themselves in Specially Designated Nationals List of the U.S. Department of the Treasury. At the same time the concept of secondary sanctions as well as empirical reflections of their use hardly enjoy satisfactory reflection in the academic literature. The purpose of the article is to fill in this gap. Key research questions concern the intensity of the use of the U.S. secondary sanction in relation to Russia, the main reasons of their use against particular persons, the distribution of sanctioned persons in terms of country of origin and other variables. Main hypothesis implies the quantitative rise of sanctions related to the violation of export control and connections to already sanctions persons in such countries as China, UAE, Turkey and others. The processing of 511 cases of secondary sanctions database is the main tool to test this assumption.